Prison Chaplains: Perceptions of Criminality, Effective Prison Programming Characteristics, and the Role of Religion in the Desistance from Crime - Denney, Andrew S. (American journal of criminal justice, 2018)
Through performing a content-analysis on 19 interview transcriptions with full-time prison chaplains employed by a Midwestern state department of corrections, this study examines the beliefs of prison chaplains regarding causes of criminal offending and views on rehabilitation. Specifically, this study examines three research questions of (1) what factors do prison chaplains perceive to be causative for criminal offending; (2) what characteristics, treatment, and/or programming do prison chaplains view as essential for offenders turning away from a life of crime; and (3) what role, if any, does religion/ faith factor into one desisting from crime. For perceived reasons for criminal offending, four individual themes emerged of illicit drug-use, poor social support, a ‘criminal mind,’ and low impulse-control. For effective prison programming practices, a total of three themes emerged being programming that emphasized altering ‘criminal thinking,’ strong social support, and emphasizing morality. For the role of religion/faith in the desistance from crime, three unique themes emerged of religion/faith provides moral accountability and a sense of purpose, offers community, and that religion/faith is not necessary. Policy implications, limitations, and future directions for research are discussed.